Hungarian Monitoring, 4 November 1988 . [Magyar rádiófigyelő], 1988. november 4 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - USSR decided on military steps in Afghanistan - British prime minister Thatcher visits Poland Domestic Affairs: - Meeting of Austrian and Hungarian heads of state: joint press conference - Mátyás Szűrös in talks with president of Polish parliament Malinowski - Central Committee in session: position on domestic politics, personnel changes - Wreath-laying ceremony at Republic Square in Budapest on anniversary of formation of revolutionary workers' and peasants' government - Hungarian leaders send their greetings on the 70th anniversary of the October Revolution Economy: - Hungarian government discusses reducing support: plans would reduce price support from 130 billion to 40 billion over 4 years - Deputy director of Dutch Commercial House: it is exceptionally easy to sell in Hungary, but difficult to buy Külpolitika: - SZU katonai lépéseket határozott el Afganisztánban - Thatcher brit miniszterelnök lengyelországi látogatása Belpolitika: - Osztrák - Magyar államfői találkozó:közös sajtóértekezlet - Szűrös Mátyás tanácskozott Malinowskival, a lengyel parlament elnökével - KB ülés: állásfoglalás a belpolitikai helyzetről, személycserék - A forradalmi munkás-paraszt kormány megalakulásának évfordulóján koszorúzás volt Köztársaság-téren - A magyar vezetők üdvözletet küldtek az októberi forradalom 70. évfordulója alkalmából Gazdaság: - A magyar kormány a támogatások csökkentéséről tárgyalt, a tervek szerint négy év alatt 130 milliárdról 40 milliárdra csökkentik az ártámogatásokat - A Holland Kereskedőház igazgatóhelyettese szerint Magyarországra rendkívül könnyű eladni, vásárolni azonban nehéz